Analysis of PGMI Students’ Ability to Identify Local Wisdom Values in Children’s Literature Texts - Elfira Mahmud; Mudayanah (International journal of technology and education research, 2026)
The ability of prospective SD/MI (elementary school) teacher students to identify local wisdom values in children's literary texts varies and has not yet fully demonstrated depth in cultural analysis. This condition raises questions about the extent to which students are able to recognize and interpret the local wisdom values contained in children's literary texts. This study aims to analyze the ability of students in the PGMI Study Program to identify local wisdom values in children's literary texts. This research employed a descriptive design with a qualitative approach involving 20 students who were assigned to analyze literary texts based on local wisdom. The data were classified into three ability categories high, moderate, and low based on the accuracy of value identification, depth of analysis, and the ability to relate the values to the cultural context of Ternate. The results showed that 55% of the students were in the high category, as they were able to identify implicit values and relate them to the philosophy of Ternate traditional customs. A total of 35% were in the moderate category, demonstrating the ability to identify general moral values but not yet specifically linked to the local context. Meanwhile, 10% were categorized as low due to difficulties in determining the moral message and interpreting cultural symbols. These findings indicate that the majority of students have demonstrated good ability in identifying local wisdom values. However, strengthening instruction in children’s literature based on local culture is still necessary to enhance analytical depth and cultural sensitivity among prospective elementary/Islamic elementary school (SD/MI) teachers. The findings of this study indicate the importance of strengthening local culture based children’s literature learning for prospective SD/MI (elementary school) teachers, so that they develop stronger cultural sensitivity and deeper analytical skills in utilizing literature as a medium for character education grounded in local wisdom.